Portrait of the realist as a historian: On anti-whiggism in the history of international relations. (March 2015) - Guilhot, Nicolas
In recent years, a revisionist history of international relations theory has generated a complex and nuanced picture of classical realism. In doing so, it has also contributed, more often than not, to a normative rehabilitation of realism. Disciplinary historians, however, have been remarkably silent about the causes of their collective bias. This article explores the paradox of a disciplinary history that has often mobilized 'anti-whig' arguments in its battle against the potted history of 'great debates, ' yet only to pursue a not-so-covert presentist agenda. It argues that the revisionist history of international relations is itself part of the realist tradition, and that from its early formulation by Herbert Butterfield to its current deployment in disciplinary history, the anti-whig argument has seamlessly woven together a vision of history and a Christian-realist vision of politics. I suggest that the entanglement between realism and the historicist rejection of rationalist philosophies of history has the potential of fundamentally renewing our understanding of realism. By the same token, recovering the elective affinities between realism and historicism casts under a new light current debates about the relationship between realism and the Enlightenment since it suggests that realism was essentially a form of counter-Enlightenment.